A simple library implementation of binary sessions*. (21st December 2016) - PADOVANI, LUCA
Abstract: Inspired by the continuation-passing encoding of binary sessions, we describe a simple approach to embed a hybrid form of session type checking into any programming language that supports parametric polymorphism. The approach combines static protocol analysis with dynamic linearity checks. To demonstrate the effectiveness of the technique, we implement a well-integratedOCaml module for session communications. For free, OCaml provides us with equirecursive session types, parametric behavioural polymorphism, complete session type inference, and session subtyping.